Analysis of the dicyemid diversity using amplicon sequencing - Flegrová, Tereza (Jihočeská univerzita, 2022)
Using amplicon sequencing, this study reveals dicyemid diversity around the world as well as within individual cephalopod hosts. A wide number of samples of multiple species were collected to reflect true dicyemid diversity. Heterogeneity primers were designed in order to improve the sequencing performance of the Illumina platform. A complex bioinformatic pipeline was implemented to process non-overlapping reads. The species delimitation methods were used to categorize occurring dicyemid types. Using the output of implemented methods, dicyemid diversity was assessed, proposing new trends opposing the current methodology.
Analysis of the dicyemid diversity using amplicon sequencing
Keywords: amplikonové sekvenování; dicyemida; populační diverzita; illumina; amplicon sequencing; dicyemida; population diversity; illumina